Organizational culture and the Competitive Strategies in the cellulose, paper and cardboard industry in Mexico (2019)
The objective of this study is to analyze the possible relationship between the degree of flexibility or rigidity of the organizational culture and the use of competitive strategies in the industry of paper, cardboard and pulp in Mexico. Currently the volatile and competitive environment in which firms are inserted forces them to explore on the fundamentals that give sustenance to their organizational culture, and to study the competitive strategies that take to respond to the demands of the market, if they want to remain in them. To achieve this, a questionnaire based on Yeung, Ulrich, Nason and Von Glinow (2000) and Gomez (2008) was applied on a sample of 25 companies across the country, obtaining 420 observations. It was used to culture the focus of Cameron and Quinn (2006) and for the strategy the focus of Porter (1982). A Pearson correlation test was applied to test the hypothesis. We found that the dominant culture is the market and the dominant strategy is cost, and the construct rigid culture better associates to strategies, particularly with the differentiation and that there is evidence of the association between the two variables in the studied industry. The results found no doubt will be useful to managers in industry, and then assist them to rethink their strategies and seek to find an appropriate balance of cultural strengths. For the academic research sector found empirical results are important, because they strengthen the findings of the literature.